COMPARISON OF HEART RATE VARIABILITY ADJUSTED FOR AGE AND HEART RATE IN WOMEN WITH RHEUMATOID ARTHRITIS AND WOMEN WITHOUT RHEUMATIC DISEASES - D. S. Novikova; T. V. Popkova; A. N. Gerasimov; A. V. Volkov; E. I. Nasonov (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To compare the 24-hour indicators of heart rate variability (HRV), adjusted for age and 24-hour average heart rate (HR24) in women with rheumatoid arthritis (RA) and women of the control group.Material and methods. Women with RA (n=291) at the age of 20-60 were examined. Women without rheumatic diseases (n=125) were included into control group. The presence of traditional cardiovascular risk factors, the results of 24-hour ECG monitoring were assessed in addition to clinical symptoms, RA activity and severity. Transformation of the initial HRV parameters in their logarithms, and the standardization of the logarithms of age and HR24, the calculation of the exponential of the standardized logarithm were performed to remove the effects of age and heart rate on HRV.Results. Time and frequency HRV indices, adjusted for age and HP24 (HRVa) in women with RA were lower than these in women of control group. HRVa decline was observed in 14–24% of women with RA. The maximum HRVa decrease was observed among the parameters that reflect an activity of parasympathetic autonomic nervous system (RMSSDn, pNN50n, HFn).Conclusion. The young and middle age women with RA differ from the women of the control group in significant decrease in the time and spectral HRV indices adjusted for age and HR24.